AKULTURASI BUDAYA TEMBANG DHANDHANGGULA DALAM TRADISI TINGKEBAN MASYARAKAT TIONGHOA DI DESA KARANGTURI, LASEM - Eva Setyani; Bambang Sulanjari; Yuli Kurniati Werdiningsih (Sabdasastra : Jurnal Pendidikan Bahasa Jawa, 2025)
ACCULTURATION OF TEMBANG DHANDHANGGULA CULTURE IN THE TINGKEBAN TRADITION OF THE CHINESE COMMUNITY IN KARANGTURI VILLAGE, LASEMThis study examines cultural acculturation in the lyrics of the Macapat Dhandhanggula “Bok Tok Utama” performed in the Tingkeban tradition of the Chinese community in Karangturi Village, Lasem. The research employed a qualitative method, with data in the form of song lyrics collected through processes of translation, classification, and identification. The data were then analyzed based on metrical structure, linguistic aspects, and socio-cultural context. The findings reveal that the Dhandhanggula “Bok Tok Utama” adheres to the standard rules of macapat with consistent patterns of guru wilangan and guru lagu, despite an aesthetic variation in the fourth stanza. Linguistically, the song is dominated by Modern Javanese with the inclusion of Chinese phrases such as Khongcu and Tiong Yong, indicating intercultural interaction. These findings demonstrate that the Tingkeban tradition of the Chinese community in Karangturi not only preserves literary values but also functions as a medium of prayer and hope, reflecting the acculturation between Javanese and Chinese.